Optimization of the welding sequence and direction for the side beam of a bogie frame based on the discrete particle swarm algorithm. (June 2018) - Shao, Qing; Xu, Tao; Yoshino, Tatsuo; Song, Nan; Yu, Zhenglei
For any large weldment with many welding seams, the welding sequence and direction have a strong influence on the assembly and service performance, especially for the side beam of the bogie frame of a high-speed rail passenger car (CHR3; CRRC, Changchun, China). Because different combinations of the welding sequence and direction greatly increase the computational time and research costs, a three-dimensional finite element approach was developed to investigate the optimal welding sequence and direction. Then, a surrogate model was established by design of experiment and used the concepts of a pointer and stack. Finally, the welding sequence and direction were optimized by the discrete particle swarm optimization algorithm. The max residual deformation and stress of the optimal result were −3.92 mm and 212.56 MPa, respectively, which is approximately 22% and 38% lower than the traditional enterprise plan, respectively. Furthermore, a weighted form of the residual deformation and stress was proposed to the end of optimum comprehensive effect, and the result also had 11% and 28% reduction, respectively. The simulation result of the optimal plans well reproduced the theoretical distribution results of the residual deformation and stress. It is proven that the optimal result can improve the welding quality and process of the side beam weldment in production.